Adjustment of control in the numerical Stroop task. - Dadon, Gal; Henik, Avishai (Memory & Cognition, 2017)
In the numerical Stroop task, participants are asked to compare the physical sizes (physical task) or numerical values (numerical task) of two digits and ignore the irrelevant dimension. Participants are unable to ignore the irrelevant dimension as indicated by facilitation and interference effects. The literature suggests that there is asymmetry in the ability to adjust control in the physical and numerical tasks. The present study examined this suggestion in two experiments in which we manipulated the proportion of neutral/congruent trials in an experimental block. In addition, we examined the effects of control adjustment on the resolution of the task and informational conflicts. Our results suggest that adjustment of control can be bidirectional and is dependent on task requirements. Moreover, it might be easier to inhibit irrelevant information than to inhibit irrelevant task activation.